Left Atrial Appendage Ligation Using the AtriClip Device: Single-Center Study of Device Safety and Efficacy. Issue 3 (May 2022) - Kiankhooy, Armin; Liem, Bing; Dunnington, Gansevoort H.; Pierce, Carolyn; Eisenberg, Susan J.; Burk, Shelby; Kaiser, Daniel W.; Lyons, Timothy; Huber, Daniel
Objective: Left atrial appendage (LAA) occlusion at the time of cardiac surgery in patients with atrial fibrillation has been shown to reduce the incidence of postoperative embolic stroke. However, the optimal method for LAA occlusion is not universally accepted. We sought to examine the safety and effectiveness of LAA occlusion with the AtriClip epicardial occlusion device.Methods: Cardiac surgical patients with atrial fibrillation who underwent LAA AtriClip placement were evaluated prospectively. Clip placement and clinical outcomes were examined after 1 year of follow-up with transesophageal echocardiography (TEE). The presence of a 10 mm or greater residual pouch, presence of flow into the LAA, or device-related thrombus (DRT) were considered failures.Results: Ninety-seven patients were analyzed. The mean CHA2 DS2 -VASc score was 2.4 ± 1.4. The postoperative follow-up period ranged from 366 to 1, 693 days (mean 685 days or 1.87 years). Seventy-four AtriClips were placed with video-assisted thoracic surgery, whereas 23 were placed via sternotomy or thoracotomy. Successful closure was found in 96% (93 of 97) of patients at follow-up. Failure occurred in 4 patients. No clip migration or DRT was seen on 3-dimensional imaging. Of all 97 patients, 76 (78%) were on presurgical oral anticoagulation, whereas 5 (5.1%) were on postprocedure oral anticoagulation. There were no postoperative thromboembolic events at the time of the study TEE.Conclusions: The AtriClip epicardial surgical occlusion device can provide an excellent rate of successful closure of the LAA during surgical ablation procedures without DRT.